THE IMPORTANCE OF A WELL FOUNDATION PROJECT EXECUTED IN CONSTRUCTIONS (REMUNOM, 2024)
Foundations play a fundamental role in any construction. A detailed analysis of the soil in the area intended for the construction is crucial, as it is the soil that will support the load of the building. The absence of adequate geotechnical studies can result in poorly dimensioned or oversized foundation projects. In addition, the lack of quality control in materials, labor and dimensioning of structural elements can contribute to the emergence of pathological manifestations, generating concerns among residents and leading to the review of the professionals involved in the execution of the work.